2022
DOI: 10.1007/s10784-022-09568-5
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of global climate change governance research: taking stock and moving forward

Abstract: Research on global climate change governance is no longer primarily concerned with the international legal regime, state practice and its outcomes, but rather scrutinizes the intricate interactions between the public and the private in governing climate change. This broad trend has also taken center stage within the pages of INEA. Two decades after its establishment, we sketch the main theoretical debates, conceptual innovations and empirical findings on global climate change governance and survey the new gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 118 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…The present study also found that "climate change" was among the top three cited keywords, and it was first mentioned in 2005. We believe that during this time, climate change issues became more visible because worldwide climate change forums shifted (Demekas, Grippa, 2021;Pattberg et al, 2022). Consequently, more researchers began drawing relationships to coral bleaching and climate change (Boonnam et al, 2022;Hannah, 2022;van Woesik et al, 2022).…”
Section: Significance Of the Resultsmentioning
confidence: 99%
“…The present study also found that "climate change" was among the top three cited keywords, and it was first mentioned in 2005. We believe that during this time, climate change issues became more visible because worldwide climate change forums shifted (Demekas, Grippa, 2021;Pattberg et al, 2022). Consequently, more researchers began drawing relationships to coral bleaching and climate change (Boonnam et al, 2022;Hannah, 2022;van Woesik et al, 2022).…”
Section: Significance Of the Resultsmentioning
confidence: 99%
“…Their scale, impact, and scope pose serious challenges to human society. How to respond more effectively to climate change is a major strategic issue involving both national self-interest and the common interests of all humankind, and both immediate and long-term interests [11,12]. According to the 30-year historical evolution of global climate governance, there are four main challenges: insufficient emission reductions, leadership deficit, imperfect governance institutions, and increased uncertainty and instability in the international environment [13,14].…”
Section: Introductionmentioning
confidence: 99%